THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY ON EMPLOYEE PUBLIC AND WORK ENVIRONMENT ON JOB SATISFACTION AT TRANS INDO PRINCIPAL (TIU) RANTAUPRAPAT - Putri Ananda Harahap; Likdanawati; Yanita; Khairawati (RADJA PUBLIKA, 2024)
The purpose of this research is to determine the effect of corporate social responsibility (X 1 ) on job satisfaction (Y) at PT. Trans Indo Utama (TIU) Rantauprapat. To determine the effect of corporate social responsibility to society (X 2 ) on job satisfaction (Y) at PT. Trans Indo Utama (TIU) Rantauprapat. To determine the effect of corporate social responsibility on the work environment (X 3 ) on job satisfaction (Y) PT. Trans Indo Utama (TIU) Rantauprapat. Corporate social responsibility is an aspect that must be considered in increasing job satisfaction. The corporate social responsibility that is the focus of the research is related to employees, society and the work environment. Meanwhile, job satisfaction will lead to performance and increased work effectiveness, which is oriented towards a company's profits. The sample in this research was 139 employees of PT. Trans Indo Utama (TIU) Rantauprapat. The data analysis techniques used in this research are descriptive analysis and multiple linear regression analysis. The results of this study explain that the influence of corporate social responsibility on employees (X 1 ), society (X 2 ), and work environment (X 3 ) positive and significant effect on satisfaction Work (Y). Overall job satisfaction will make the company's development faster.